Noradrenaline enhances the excitatory effects of dopamine on medial prefrontal cortex pyramidal neurons in rats. Issue 4 (8th September 2020) - Shinohara, Fumiya; Arakaki, Saya; Amano, Taiju; Minami, Masabumi; Kaneda, Katsuyuki
Abstract: Aim: Our previous studies showed that exposure to acute restraint stress enhanced cocaine‐induced conditioned place preference (cocaine‐CPP) and suggested the possibility that co‐activation of adrenergic transmission boosts the increase in medial prefrontal cortex (mPFC) neuronal activity by the activation of dopaminergic transmission. To examine this possibility, the effects of the co‐treatment with dopamine (DA) and noradrenaline (NA) on mPFC neurons were compared with those of treatment with DA alone using whole‐cell patch‐clamp recordings. Methods: The effects of DA alone and a mixture of DA and NA on the membrane potentials and spontaneous excitatory postsynaptic currents (sEPSCs) were examined by electrophysiological recordings of mPFC pyramidal neurons in brain slices of male Sprague Dawley rats. Extracellular DA and NA levels in the mPFC during and after restraint stress exposure were also examined by in vivo microdialysis. Results: Dopamine significantly produced depolarizing effects on mPFC neurons and tended to increase sEPSC frequency. Co‐administration of NA with DA produced stronger depolarizing effects and significantly increased sEPSC frequency. The findings suggest that the additional depolarizing effect of NA on DA‐responsive neurons, rather than the excitation of DA‐nonresponsive neurons by NA, contributes to the stronger effect of co‐treatment of NA with DA. Conclusion: The present study suggests that NA released by restraint stress exposure cooperates with DA to stimulate DA‐responsive neurons in the mPFC, thereby causing the stress‐induced enhancement of cocaine‐CPP. Abstract : Our previous studies showed that exposure to acute restraint stress enhanced cocaine‐induced conditioned place preference (cocaine‐CPP). The present study revealed that noradrenaline enhanced the excitatory effects of dopamine on medial prefrontal cortex (mPFC) pyramidal neurons in rats. Noradrenaline released by restraint stress exposure may cooperate with dopamine to stimulate dopamine‐responsive neurons in the mPFC, thereby causing the stress‐induced enhancement of cocaine‐CPP.